Model ekspansi matriks asal tujuan perjalanan angkutan umum - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT This paper presents the development of a simplified model of the expansion of public transport origin - destination (OD) matrix. OD matrix should be based on a proper zone size in order to generate a realistic trip pattern. The model aims at expanding matrix based on coarse zones into a new matrix based on fine sub zones. The model relies on the estimation of generation factors of each sub zones. Besides, the distributed trips are constrained by estimated willingness-to-walk distance of public transport users.